Synthesis of Sulfated and CaO-Modified UiO-66 Bifunctional Catalysts from Zircon Sand for Conversion of Waste Cooking Oil - Pasaribu, Marvin Horale; Agnestisia, Retno; Pratika, Remi Ayu; Toepak, Erwin Prasetya; Karelius , Karelius (Chempublish Journal, 2026)
Zircon-based UiO-66 metal–organic frameworks (MOFs) were synthesized from Central Kalimantan zircon sand and modified into bifunctional catalysts for two-step biodiesel production from waste cooking oil (WCO). Zirconium oxychloride (ZrOCl₂·8H₂O), obtained via acid leaching of zircon sand, served as the precursor for solvothermal UiO-66 synthesis using terephthalic acid (H₂BDC) as a linker. Post-synthetic modifications yielded sulfated UiO-66 (UiO-66/SO₄) as an acid catalyst and CaO-modified UiO-66 (UiO-66/CaO) as a base catalyst. XRD analysis displayed sharp reflections at 2θ = 7.4°, 8.5°, 25.8°, and 30.8° for UiO-66, with additional peaks at 17.7°, 33.8°, and 46.8° corresponding to CaO and Ca(OH)₂ phases, and a new band at 1114 cm-1 confirming sulfate incorporation—indicating successful formation of acid–base composite structures. Catalytic tests were conducted at varying catalyst loadings of 0.25%, 0.5%, and 0.75%. The UiO-66/SO₄ catalyst achieved the highest esterification efficiency at 0.5% loading, reducing the free fatty acid (FFA) content by 51.7%. Similarly, UiO-66/CaO exhibited optimum transesterification activity at 0.5% loading, yielding 61.82% biodiesel. FTIR spectra of the products confirmed fatty acid methyl ester (FAME) formation with characteristic C=O (1744 cm-1), C–O (1165, 1031 cm-1), and CH₃ (1456 cm-1) vibrations. These results demonstrate that zircon-sand-derived UiO-66 catalysts possess excellent structural stability, synergistic acid–base functionality, and strong catalytic efficiency, providing a sustainable pathway for biodiesel production from waste cooking oil